Respuesta :

Answer:

C. (5, -3)

Step-by-step explanation:

4x + 3y = 11

x - y = 8  (multiply by 3) --> 3x - 3y = 24


4x + 3y = 11

3x - 3y = 24

---------------------add

7x = 35

 x = 5


5 - y = 8

y = 5 - 8

y = -3

(5, -3)


Answer:

C. (5, -3)

Step-by-step explanation:

Rewrite the first equation.

Multiply the second equation by 3 and write it under the first equation.

4x + 3y = 11

3x - 3y = 24

Now add the equations.

7x        = 35

Divide both sides by 7.

x = 5

Substitute 5 for x in the original first equation:

4(5) + 3y = 11

20 + 3y = 11

3y = -9

y = -3

Solution: (5, -3)